Clinical profile, management, and outcome of obstructive jaundice patient at a tertiary care center: A prospective study - Gulab Dhar Yadav; Anju Yadav; Shraddha Verma; Mohammad Tahir Hussain (Asian Journal of Medical Sciences, 2022)
Background: There are various causes of obstructive jaundice, choledocholithiasis is the commonest cause. Patients with obstructive jaundice need early diagnosis to established level and nature of obstruction in biliary system. The history and clinical examination in arriving at a correct pre-operative diagnosis in almost always possible today because of advances in imaging techniques over the decades. Presents study attempts to determine the various causes, age and sex pattern in Extra Hepatic obstructive jaundice. Aims and Objectives: The aim of the study was to study clinical profile, management, and outcome of obstructive jaundice, patient at a tertiary care center: A prospective study. Materials and Methods: The present hospital based prospective interventional study was conducted on patients with obstructive jaundice, those were admitted in the Department of General Surgery at GSVM Medical College Kanpur, patients of age more than 12 years both sex after obtaining the consent form the patient or their relatives were studied during the period of study from January 2020 to October 2021. Results: Of the 50 patients; 29 (58%) were female and 21 (42%) were male, their mean age being 51.10 years. Malignant obstructive jaundice was seen in 19 (38%) patients while 31 (62%) had benign etiology. Amongst the obstructive jaundice cases; pain in abdomen (100%) was commonest symptoms and icterus (100%) was the most common sign. The most common malignancy was Carcinoma (Ca) of the head of pancreas 09 (18%) followed by distal common bile duct (CBD) cholangiocarcinoma 04 (08%), and hilar cholangiocarcinoma 03 (06%). Choledocholithiasis 25 (50%) was the most common benign cause followed by benign stricture of common bile duct 03 (06%). Conclusion: Obstructive jaundice is one of the common causes of surgically amenable jaundice. Its etiology is varied and diagnosis usually depends on appropriate imaging. Proper diagnosis and treatment is necessary as delay in the diagnosis may cause irreversible pathological changes causing increased morbidity and mortality.